Temperature-dependent performance of LRBs and its effect on seismic responses of isolated bridges under near-fault earthquake excitations. (July 2022) - Fu, Jian-Yu; Cheng, Hu; Wang, Dong-Sheng; Zhang, Rui; Xu, Ting-Ting
Abstract: As the widely used seismic isolators in engineering structures, the mechanical property of lead rubber bearings (LRBs) is vital to the seismic performance of isolated structures. Due to cyclic loadings, the temperature of lead core raises, causing the performance degradation of LRBs. This paper investigates the seismic performance of isolated bridges with consideration of the temperature-dependent behavior of LRBs, and the seismic responses of isolated bridges are quantified based on both the energy and deformation. The analytical results indicate that the absorbed energy and shearing strain of bearings increase when considering the effect of lead core heating under seismic loadings, and these variations cannot be ignored. Besides, the relative variations of energies and deformations of isolated bridges are unrelated to the period of the velocity pulse of near-fault ground motion. The temperature-dependent behavior of LRBs under seismic loadings is suggested to be taken into account in the seismic design of isolated bridges. Otherwise, the seismic damage risk of isolated bridges will be underestimated significantly.